2020
DOI: 10.3389/fpubh.2020.604339
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 Mortality: A Matter of Vulnerability Among Nations Facing Limited Margins of Adaptation

Abstract: Context: The human development territories have been severely constrained under the Covid-19 pandemic. A common dynamics has been observed, but its propagation has not been homogeneous over each continent. We aimed at characterizing the non-viral parameters that were most associated with death rate. Methods: We tested major indices from five domains (demography, public health, economy, politics, environment) and their potential associations with Covid-19 mortality during the first 8 months of 2020, through a P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 36 publications
2
62
0
3
Order By: Relevance
“…Possible explanations for these significant differences may be related to the magnitude of deaths in these countries. After October 2020, when our study was published in a preprint server for Health Sciences, new articles were published with similar results 51 – 54 .…”
Section: Discussionmentioning
confidence: 79%
“…Possible explanations for these significant differences may be related to the magnitude of deaths in these countries. After October 2020, when our study was published in a preprint server for Health Sciences, new articles were published with similar results 51 – 54 .…”
Section: Discussionmentioning
confidence: 79%
“…There must be greater national and international sensitivity to how restrictive measures impact human movement ( 20 , 21 ). Indeed, a recent article investigating non-viral parameters associated with death rate, researchers found that the national criteria most associated with death rate were: life expectancy (and its slowdown), a public health context [e.g., metabolic and non-communicable diseases (NCD) burden vs. infectious diseases prevalence], the economy (e.g., growth national product, financial support), and the environment (e.g., temperature) ( 22 ). Enforcing strict measures to fight the COVID-19 pandemic, including lockdown, were not linked with death rate, and moreover, the authors suggested that a better understanding of the inherent factors which affect COVID-19 mortality may improve prevention strategies, one of which was highlighted as increasing population immune resilience through better physical fitness ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“… 6 ; 7 ; 9 ; 15 ; 28 ; 29 ; 36 ; 40 ; 41 ; 43 ; 44 ; 46 ; 53 ; 56 ; 57 ; 59 ; 60 ; 72 ; 75 ; 76 ; 83 ; 84 ; 87 ; 88 ; 90 ; 91 ; 92 ; 96 ; 118 ; 119 ; 121 ; 122 ; 129 ; 133 ; 136 ; 146 ; 147 ; 148 ; 149 ; 150 ; 152 ; 162 ; 163 ; 164 ; 165 ; 166 ; 167 ; 168 ; 169 ; 177 ; 181 ; 182 ; 183 ; 184 ; 196 ; 197 ; 206 ; 207 ; 208 ; 209 ; 211 ; 212 ; 218 ; 219 ; 220 ; 221 ; 222 ; 223 ; 224 ; 225 ; 235 ; 236 .…”
Section: Uncited Referencesunclassified